Function of sildenafil on diseases other than urogenital system: An umbrella review - Chen, Zeyu; Huang, Yin; Cao, Dehong; Qiu, Shi; Chen, Bo; Li, Jin; Bao, Yige; Wei, Qiang; Han, Ping; Liu, Liangren (Frontiers in Pharmacology, 2023)
We conducted an umbrella review based on existing pooled evidence (systematic reviews and meta-analyses) to assess the quality of evidence, validity and biases of the therapeutic functions of sildenafil on multiple diseases. Thirty-three outcomes were extracted from 1163 published papers. According to the data we extracted from this evidence, sildenafil achieved significant therapeutic effects on cardiovascular, pulmonary, pulmonary-arterial, and umbilical hemodynamics and diabetes-related vascular diseases.